Perbandingan Akurasi Pengukuran Sensor LM35 dan Sensor DHT11 untuk Monitoring Suhu Berbasis Internet of Things - Sirojul Hadi; Radimas Putra Muhammad Davi Labib; Parama Diptya Widayaka (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2022)
Temperature is an object of research that is often studied. Research on temperature is within the scope of control and monitoring. The process of controlling and monitoring temperature is influenced by the selection of the right temperature sensor. The temperature sensors that are often used are the LM35 sensor and the DHT11 sensor. The LM35 sensor has advantages in terms of a simple design and easy to implement, while the DHT11 sensor has the advantage because in one sensor package there are two functions, namely to measure air temperature and humidity. In this study, temperature measurement accuracy was carried out to facilitate researchers in determining the right temperature sensor. The data monitoring method uses the internet of things (IoT). The results of the research show that the DHT11 temperature sensor is more accurate and more stable than the LM35 temperature sensor. The results of the sensor test at room temperature, the DHT11 sensor has an accuracy rate of 97.21% while the LM35 sensor has an accuracy rate of 96.86%. While the results of the sensor test in the server room, the DHT11 sensor has an accuracy rate of 95.26%, while the LM35 sensor has an accuracy rate of 90.32%.